Nanomechanics of multidomain neuronal cell adhesion protein contactin revealed by single molecule AFM and SMD - Mikulska-Ruminska, Karolina (Sci Rep, 2017)
Contactin-4 (CNTN4) is a complex cell adhesion molecule (CAM) localized at neuronal membranes, playing a key role in maintaining the mechanical integrity and signaling properties of the synapse. CNTN4 consists of six immunoglobulin C2 type (IgC2) domains and four fibronectin type III (FnIII) domains that are shared with many other CAMs. Mutations in CNTN4 gene have been linked to various psychiatric disorders. Toward elucidating the response of this modular protein to mechanical stress, we studied its force-induced unfolding using single molecule atomic force microscopy (smAFM) and steered molecular dynamics (SMD) simulations. Extensive smAFM and SMD data both indicate the distinctive mechanical behavior of the two types of modules distinguished by unique force-extension signatures. The data also reveal the heterogeneity of the response of the individual FNIII and IgC2 modules, which presumably plays a role in the adaptability of CNTN4 to maintaining cell-cell communication and adhesion properties under different conditions. Results show that extensive sampling of force spectra, facilitated by robot-enhanced AFM, can help reveal the existence of weak stabilizing interactions between the domains of multidomain proteins, and provide insights into the nanomechanics of such multidomain or heteromeric proteins.